RANCANG BANGUN PROTOTYPE PLTMH DENGAN TURBIN PELTON SEBAGAI MODUL PRAKTIKUM - I Gusti Putu Andhita Mahayana; Lie Jasa; I Gusti Ngurah Janardana (Program Studi Teknik Elektro UNUD, 2020)
Learned about the use of water resources as a micro hydro power plant is very importantto be carried out by Electrical Engineering students at Udayana University. At this time atConvertion Energy Laboratory there was not been a practicum about Mycro Hydro Power Plandue to the unavailability of guide practicum module and micro hydro power plant prototypes.Therefore in this research was design and build a Prototype of Microhydro Power Plan wich had18 buckets where had 5 cm width, 4,47 cm length, 1,6 height and the tickness was 0,28 cm.This prototype can made 4,5 L/s water discharge, 9,809 W Power, and the torque was 0,26 Nm. So that prototype had 1,48% efficiency. To make this prototype as a complete practicummodule was arranged practicum guide modules that was explain abaout Characteristic of MicroHydro Power Plan with Pelton Turbines.